Effect of canal irrigation with EDTA and citric acid on microleakage time in human single-rooted teeth with the use of Real-Seal system - Zahra Keivan; Behnaz Barekatain; Alireza Farhad (Isfahan University of Medical Sciences, 2011)
Introduction: Methods of root canal obturation, materials used and elimination of the smear layer have important roles in sealing the root canal system. This study compared the sealing ability of a resin-based sealer (Real-Seal) used with three different root canal irrigation protocols to remove the smear layer. Materials and Methods: In this experimental study, 85 single-rooted extracted human teeth were selected. After root canal preparation, the teeth were randomly divided into 5 groups: three experimental groups of 25 and two positive and negative control groups of 5 teeth. The final irrigants in groups 1, 2 and 3 were 17% EDTA + NaOCl, 7% citric acid + NaOCl and 20% citric acid + NaOCl, respectively. All the groups were obturated with Real-Seal system except for the 5 positive control teeth. All the teeth were kept in an incubator for 48 hours. Root surfaces were covered with nail varnish except for the apical 2 mm. After 48 hours in the incubator, the roots were assembled in the system designed for this experiment, sterilized with ethylene oxide gas and transferred to BHI (Brain Heart Infusion) in an aseptic condition. A fresh solution of Enterococcus faecalis was injected into the system every 3 days. The samples were evaluated daily for 90 days and the time of turbidity was registered in each case. Kaplan-Meier test was used for data analysis.(α =0.05)Result: There were no significant differences between the experimental groups (P value > 0.05). The longest and shortest microleakage mean times were observed in the 20% citric acid and 17% EDTA groups, respectively.Conclusion: Real-Seal system with its resin-based sealer in association with 20% citric acid irrigation is recommended for root canal treatment. Key words: Root canal therapy, Canal irrigation, Microleakage, Real-Seal System, Smear layer.